IDEOLOGICAL FRAMING OF TWO SENATORS TOWARD BIDEN’S PALESTINIAN IMMIGRATION PLAN - Fadllur Rohmah Ziyadatur Rosyidah; I Dewa Putu Wijana (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The ongoing conflict between Israel and Palestine after October 7 exacerbates, currently becoming the world’s most alarming issue. In the United States, which has an intimate relationship with Israel for providing arms and funds, American pro-Palestinian citizens march to the streets to chastise the government’s stance that bestows the wrong side. The endless action prompted Biden to consider the Palestinians entering the United States, which triggered the Republicans and Democrats to take sides, either to humiliate or support Biden’s manoeuvre. The political polarization related to Biden’s breakthrough became an enthralling topic delivered by politicians in their press releases, debates, or interviews. This study examines the contradictory ideological framing of the Republican and Democratic Senators toward the Palestinian immigration plan. The authors analyzed the interviews of Republican Senator Mitch McConnell and Democratic Senator Bernie Sanders, taken from YouTube, using a CDA approach. The transcribed interviews were observed to unveil the stylistic, syntactic, and semantic elements aimed at uncovering these senators’ ideological biases. The study, which focuses merely on van Dijk’s micro-textual structures, shows that McConnell rarely utilized stylistic and syntactic elements but heavily relied on actor description and evidentiality. In contrast, Sanders heavily applied dysphemism and example/illustration strategies.